PENGARUH ILMU GASTRONOMI SEBAGAI DAYA TARIK MINAT MAHASISWA PADA BIDANG STUDI PENDIDIKAN TATA BOGA - Hikmawati, Elma Nur; Martiningtyas, Anggi (Journal of Food Technology and Agroindustry, 2024)
The purpose of this study was to determine the influence of gastronomy as the attractiveness ofrespondents before entering the food and beverage industry with their sustainability as studentsafter taking the field of culinary education. This study uses descriptive and quantitativeresearch methods with primary data collection techniques using a questionnaire withinformants of 50 undergraduate Education and D3 Catering students from the 2020 and 2021classes. The results are (1) 54% of students are interested in exploring culinary science basedon gastronomy obtained through taste, decoration of food (platting), processing, andpreparation of food & beverage. (2) 98% of students want to continue the culinary knowledgethat has been obtained by (3) applying the amount of 40% as entrepreneurs, (4) 36% workingin restaurants, hotels or other tourism sectors, (5) 12% becoming educators, and (6) The same6% open courses and work in food & beverage companies. The conclusion is that gastronomyas a good study in enjoying food & drinks is a factor that supports the interest of respondentsbefore and after becoming a student in the culinary education department. This research is alsosupported based on research journals by; Jefriyanti, Ranti (2017) and Rosyadi, Yusril Fahmi(2020).